The Effect of Crystal Mismatch on the Thermoelectric Performance Enhancement of Nano Cu2Se - Demirci, Yunus; Yusuf, Aminu; Hamawandi, Bejan; Toprak, Muhammet S.; Ballikaya, Sedat (Frontiers in Materials, 2021)
In the past decades, Cu2-xSe compounds have attracted great attention due to inclusion of non-toxic and abundant elements, besides having a promising thermoelectric (TE) performance. In this work, we investigated the effect of crystal mismatch of a nanoinclusion phase on the TE properties of Cu2-xSe. Nano-Cu2Se was synthesized using microwave assisted thermolysis, while the p-type skutterudite, Fe3.25Co0.75Sb12 (FeCoSb), compound was synthesised using chemical alloying route. Nano-Cu2Se, and (nano-Cu2Se)1-x(nano-FeCoSb)x composites, where x = 0.05 and 0.1, were prepared via mechanical alloying followed by Spark Plasma Sintering (SPS) process. Structural properties were evaluated by PXRD and SEM analysis, while the high temperature transport properties were examined via electrical conductivity, Seebeck coefficient, and thermal conductivity measurements in the temperature range of 300-800 K. Powder X-ray diffraction (PXRD) confirmed single phase of nano Cu2Se, while the samples with FeCoSb inclusion consist of two phases as Cu2Se and CoSb3. SEM micrographs of all samples show that Cu2Se has randomly oriented grains with different size. Cu2Se samples with FeCoSb inclusion show a rather different structure. In these samples, rod-shaped FeCoSb phase, with size varying between 20-100 nm, showed an inhomogeneous distribution in the structure and stacked between the Cu2Se layers. Transport data indicate that crystal mismatch between Cu2Se and FeCoSb has a strong effect on the TE transport properties. Electrical conductivity decreases but Seebeck coefficient enhances with nano FeCoSb inclusion. Total thermal conductivity was suppressed by 30% and ZT value enhanced by 15% with 5% nano FeCoSb inclusion at 750 K, likely due to a decrease in the electronic contribution of the thermal conductivity. Structural and transport data show that small amount of nanoinclusion of FeCoSb have beneficial effect on the TE performance of nano Cu2Se at temperatures below 800 K.